A biomineralization barrier for sealing bedrock fissures to control contaminant matrix back diffusion and a system for constructing the same
Patent Information
- Application Number
- CN202611094510.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-27
AI Technical Summary
1、由于本申请采用了产脲酶菌和氨氧化菌复配的复合功能菌剂,并配合三阶段序贯注入工艺,实现了在封堵裂隙的同时,将代谢副产物铵根离子原位转化为无害的硝酸根离子,因此获得了高效封堵且无二次污染的技术效果。
Abstract
Description
Technical Field
[0001] This application relates to the fields of environmental engineering and groundwater remediation technology, and more specifically, it relates to a biomineralization barrier and its construction system for sealing bedrock fissures and controlling the back diffusion of pollutant matrix. Background Technology
[0002] In remediation projects involving contaminated sites, especially those involving low-permeability bedrock fissures, "matrix backdiffusion" refers to the slow diffusion of pollutants from the micropores of low-permeability bedrock into the purified groundwater area after remediation. This causes remediation targets to be repeatedly exceeded, resulting in an expensive "tailing effect."
[0003] Existing technologies face three main challenges: First, sealing materials are difficult to penetrate and remain in. Traditional grouting materials, such as cement and silicate gel, have large particle sizes and high viscosity, making them unable to effectively penetrate micron-sized cracks. Second, the sealing effect is not long-lasting. Physicochemical sealing bodies are prone to failure due to groundwater chemical erosion or changes in geological stress. Third, the repair process lacks selectivity and may damage hydrogeology.
[0004] In bio-plugging technology, microbial-induced calcium carbonate precipitation is a promising method, but its direct application to bedrock fissures faces key challenges: functional microorganisms struggle to colonize and exhibit low activity in the anaerobic and nutrient-poor fissure environment; conventional bacterial solutions are significantly lost after injection; the biomineralization process is uncontrollable, easily leading to rapid crystallization near the injection point, resulting in "sealing" rather than deep plugging; furthermore, the traditional MICP process uses urea as a substrate, generating NH4. + Byproducts cause secondary pollution. Summary of the Invention
[0005] In order to achieve deep, uniform, and permanent sealing of bedrock fissures and prevent secondary pollution at the source, this application provides a biomineralization barrier and its construction system for sealing bedrock fissures and controlling the back diffusion of pollutant matrix.
[0006] In a first aspect, this application provides a system for constructing a biomineralization barrier to seal bedrock fissures and control the back diffusion of pollutant matrix, employing the following technical solution: A system for constructing a biomineralization barrier to seal bedrock fissures and control the back diffusion of pollutant matrix, comprising: The slurry preparation and injection unit is used to prepare and inject biomineralized slurry; the biomineralized slurry contains a composite functional bacterial agent and a multi-level functional carrier, the composite functional bacterial agent contains urease-producing bacteria and ammonia-oxidizing bacteria, and the multi-level functional carrier includes micron-sized biochar carrier and nano-sized silica carrier. The slurry preparation and injection unit includes at least: a preparation device for providing slurry preparation space, an injection device for delivering slurry to the target fracture zone, and a control device connected to the injection device for adjusting injection parameters. Distributed monitoring nodes are a network of monitoring wells deployed upstream and downstream of the target fracture zone; The feedback control terminal is communicatively connected to the control device and the monitoring node, and is used to adjust the injection parameters of the slurry preparation and injection unit.
[0007] By adopting the above technical solution, the controllable preparation and injection of biomineralized slurry is achieved through a slurry preparation and injection unit. Distributed monitoring nodes acquire real-time hydrochemical and hydraulic response information of the fracture zone, and the injection parameters are dynamically adjusted through a feedback control terminal, forming a closed-loop construction system of "preparation-injection-monitoring-control". This system can adaptively adjust the slurry composition and injection strategy based on real-time feedback of the fracture zone's heterogeneity, providing a hardware foundation for a three-stage sequential injection process. This ensures that functional microbial agents and carrier materials can be targeted and delivered deep into the fractures, achieving deep and uniform sealing.
[0008] Preferably, the distributed monitoring node includes a monitoring probe for real-time acquisition of pH value, conductivity, calcium ion concentration, ammonium ion concentration and nitrate ion concentration.
[0009] By adopting the above technical solution, multi-parameter monitoring probes are integrated into the distributed monitoring nodes, enabling in-situ, continuous, and real-time acquisition of key hydrochemical indicators within the bedrock fracture zone. Among these, pH reflects the acid-base environment of the mineralization reaction system, directly affecting the dissolution-precipitation equilibrium of calcium carbonate precipitation and the metabolic activity of microorganisms; conductivity can be used to indirectly characterize changes in the total ion content of the slurry, aiding in the assessment of slurry diffusion and dilution behavior; calcium ion concentration is a direct substrate parameter of the mineralization reaction, and its consumption rate and spatial distribution accurately reflect the reaction progress of calcium carbonate precipitation; ammonium ion concentration and nitrate ion concentration correspond to the production of urease-producing bacteria metabolites and ammonia-oxidizing bacteria conversion products, respectively, together constituting an immediate evaluation indicator of the effectiveness of secondary pollution elimination.
[0010] Secondly, this application provides a method for using a system for constructing a biomineralization barrier to seal bedrock fissures and control the back diffusion of pollutant matrix, employing the following technical solution: A method for using a system for constructing a biomineralization barrier to seal bedrock fissures and control the back diffusion of pollutant matrix includes the following steps: S1. Prepare a composite functional bacterial agent and a multi-level functional carrier, wherein the composite functional bacterial agent contains urease-producing bacteria and ammonia-oxidizing bacteria, and the multi-level functional carrier includes a micron-sized biochar carrier and a nano-sized silica carrier. S2. A three-stage sequential injection process is used to inject sequentially into the target bedrock fracture zone: The first stage slurry includes the aforementioned composite functional bacterial agent, nanocarrier, and microbial activation nutrient solution; The second stage slurry includes the micron-sized carrier, the composite functional bacterial agent, and the microbial nutrient solution; The three-stage slurry includes a biodegradable hydrogel embedded with urea and calcium ions; S3. During the injection process, feedback control is performed based on real-time monitoring data, and the injection of slurry at each stage is completed through low-pressure pulse injection. S4. After injection, barrier maturation and curing are carried out to form a sealed plug layer of calcium carbonate cemented microbial skeleton in the bedrock fracture zone. After curing, the equivalent hydraulic conductivity is reduced by ≥2 orders of magnitude compared with the original value.
[0011] By employing the above technical solution, and using a compound functional bacterial agent composed of urease-producing bacteria and ammonia-oxidizing bacteria, the urease-producing bacteria decompose urea to produce carbonate and ammonium ions. The carbonate ions combine with calcium ions to form calcium carbonate precipitate with a cementing effect, achieving physical sealing of fissures. Simultaneously, the ammonia-oxidizing bacteria can further oxidize the ammonium ions produced by the metabolism of urease-producing bacteria into nitrate ions, eliminating the secondary pollution problem caused by traditional MIP processes at the source, and achieving an environmentally friendly biomineralization process. Utilizing hydrophobically modified nano-silica as an initial carrier, its small size effect allows it to penetrate deep into the fissures with the bacterial solution, and... First, the slurry adsorbs onto the surface of the fracture walls, providing initial attachment sites for functional microorganisms and promoting their colonization in barren environments. A three-stage sequential injection process is designed: Stage 1 injects nanocarriers and activating nutrient solution to establish an initial microbial community; Stage 2 introduces micron-sized carriers, which not only serve as the core framework for subsequent microbial growth and mineralization reactions but also construct a porous and stable microbial habitat within the fractures; Stage 3 injects biodegradable hydrogels to encapsulate the substrate, achieving slow-release and avoiding the sealing effect caused by rapid substrate consumption and excessively high local concentrations, guiding the mineralization reaction to occur uniformly along the fracture depth. Combined with low-pressure pulsed injection and feedback control, this ensures the slurry gradually fills the fractures, preventing high pressure from damaging the hydrogeological structure. Finally, the dense biological barrier formed through curing, with calcium carbonate as the cement and biochar as the framework, reduces the equivalent hydraulic conductivity of the fracture zone by more than two orders of magnitude, achieving long-term and stable sealing of back-diffusion pollutants from the matrix.
[0012] Preferably, the volume ratio of the urease-producing bacteria to the ammonia-oxidizing bacteria is 2:1; the concentration of the urease-producing bacteria in the bacterial solution is ≥5×10⁻⁶. 8 CFU / mL, urease activity not less than 3.0 U / mL; the bacterial concentration of the ammonia-oxidizing bacteria ≥ 1×10⁻⁶. 8CFU / mL.
[0013] By adopting the above technical solutions, micron and nano-carriers with specific functions were selected. Hydrogen peroxide or potassium permanganate-modified biochar was chosen as the micron carrier. After oxidation modification, the oxygen-containing functional groups on the surface of the biochar significantly increased, which not only enhanced the adhesion of Ca... 2+ The adsorption capacity of metal ions provides nucleation sites for mineralization reactions and enhances its hydrophilicity and biocompatibility, which is conducive to the attachment and growth of microorganisms. Its particle size of 20-100 μm allows it to effectively bridge and retain microorganisms in fissures, forming a stable microscopic framework. Hydrophobically modified silica, with a particle size of less than 500 nm, is used as a nanocarrier, ensuring excellent penetration ability and reaching even the smallest corners of fissures. The hydrophobic modification gives its surface a certain degree of lipophilicity, enabling it to preferentially adsorb onto the bedrock surface and assisting the functional bacterial agents in rapidly colonizing at the rock-water interface, constructing the initial biofilm. The combined use of these two carriers constructs a multi-layered, structurally stable microbial habitat from the nanoscale to the microscale.
[0014] Preferably, in step S1, the micron-sized carrier is modified biochar with a particle size of 20-100 μm, which is obtained by modification with hydrogen peroxide or potassium permanganate; the nano-carrier is hydrophobic modified silica with a particle size of <500 nm, which is silica modified with silane coupling agent surfactant.
[0015] By adopting the above technical solution, the composition and activity of the compound functional bacterial agent were further optimized. The volume ratio of urease-producing bacteria to ammonia-oxidizing bacteria was limited to 2:1, which is based on the matching relationship of their metabolites. The ammonium ions produced by the decomposition of urea by urease-producing bacteria serve as the substrate for the metabolism of ammonia-oxidizing bacteria. This ratio allows the production rate of ammonium ions to reach a dynamic balance with the consumption rate of ammonia-oxidizing bacteria, avoiding excessive accumulation of ammonium ions or inactivation of ammonia-oxidizing bacteria due to insufficient substrate. At the same time, limiting the urease-producing bacteria to have a high concentration and high urease activity ensures a sufficiently strong mineralization capacity to form a dense barrier. Limiting the ammonia-oxidizing bacteria to a high concentration ensures their efficient conversion capacity of the by-product ammonium ions. The synergy of these three factors ensures that the entire biomineralization process is efficient, continuous, and environmentally friendly.
[0016] Preferably, in the first stage slurry, the volume ratio of urease-producing bacteria to ammonia-oxidizing bacteria is 2:1, the concentration of nanocarrier is 0.1% (w / v), the total solute concentration of microbial activation nutrient solution is 1.0% (w / v), and the molar ratio of urea, calcium ions and phosphorus source is 10:5:1. In the second stage slurry, the amount of micron-sized carrier added is 1.5% (w / v), the volume ratio of urease-producing bacteria to ammonia-oxidizing bacteria is 2:1, the total solute concentration of the microbial nutrient solution is 1.5% (w / v), and the molar ratio of urea to calcium ions is 1:1.
[0017] By adopting the above technical solution, in the first stage, a low concentration of nanocarriers and total nutrients is used. The strong penetrating power of the nanocarriers is utilized to detect and open up the fissure network, while providing a minimum amount of activation energy for microorganisms to initially colonize on the fissure surface. The molar ratio of urea, calcium ions and phosphorus source in the nutrient solution in the first stage is 10:5:1. The introduction of phosphorus source is to promote microbial growth and energy metabolism, while the low calcium ion concentration is to induce only the formation of tiny calcium carbonate crystal nuclei in this stage to prevent premature blockage. In the second stage, the total nutrient concentration is increased and 1.5% w / v of micron-sized carriers are added. The purpose is to provide sufficient nutrition for the large-scale proliferation of microorganisms and to use micron-sized carriers to build the framework of the biological barrier. In this stage, the molar ratio of urea and calcium ions is adjusted to 1:1 to promote efficient calcium carbonate precipitation on the surface and in the pores of the biochar framework, forming a stable and highly bioactive composite sealing layer.
[0018] Preferably, in step S2, the biodegradable hydrogel is a compound system of thermosensitive hydrogel and guar gum, with a total concentration of 0.5% (w / v) and a mass ratio of thermosensitive hydrogel to guar gum of (1-3):1; the phase transition temperature of the thermosensitive hydrogel is 10-20℃.
[0019] By employing the above-mentioned technical solution, a compound system of thermosensitive hydrogel and guar gum is used. When prepared at low temperatures, the slurry has a low viscosity, making it easy to inject. After injection underground, the ambient temperature causes the thermosensitive hydrogel to undergo a phase transition and shrink, while the guar gum remains stable in an ionic environment. Together, they form a gel network with a specific porosity, encapsulating urea and calcium ions. A compound system with a total concentration of 0.5% (w / v) and a mass ratio of (1-3):1 can precisely regulate the degradation rate of the hydrogel and the substrate release half-life. This allows urea and calcium ions to diffuse outward continuously and stably, providing a continuous substrate for urease-producing bacteria deep within the fissures. This guides the uniform precipitation of calcium carbonate throughout the entire barrier framework, thus avoiding the local "sealing" problem caused by the one-time injection of substrate in traditional processes, ensuring the depth and uniformity of the sealing.
[0020] Preferably, in step S3, the pressure of the low-pressure pulse injection is less than 0.3 times the fracture hydrostatic pressure; each injection stage is divided into multiple pulse cycles, each cycle including a short injection of 1-4 hours and a long resting period of 24-72 hours.
[0021] By employing the above technical solution, the injection pressure is controlled at less than 0.3 times the hydrostatic pressure of the fracture, which is considered extremely low-pressure injection. The purpose is to prevent high pressure from damaging the natural fracture structure or causing excessive slurry diffusion, ensuring that the slurry mainly fills the fracture space through its own diffusion and capillary action. Each injection stage is further divided into multiple short-injection-long-resting pulse cycles. The short-injection period of 1-4 hours slowly replenishes the fracture with fresh bacterial solution and nutrients, preventing microorganisms from becoming inactive due to starvation. The subsequent long-resting period of 24-72 hours provides a sufficiently undisturbed environment for functional microorganisms, enabling them to stably attach, grow, metabolize, and induce mineralization reactions. This "pulsed" propulsion strategy simulates the growth pattern of biofilms in nature and is key to achieving deep, gradual, and high-quality fracture sealing.
[0022] Preferably, in step S3, the real-time monitoring data includes pH, conductivity, and Ca. 2+ Concentration, NH4 + Concentration, NO3 - Concentration and groundwater tracer breakthrough curve; the feedback control includes: When downstream monitoring point NH 4+ When the concentration rise rate exceeds 0.5 mg / L / h or the peak concentration exceeds 5 times the background value, increase the mass ratio or molar ratio of ammonia-oxidizing bacteria in the slurry to the total inoculum by 10-20% in the next stage, or extend the static culture time by 12-24 h. When mineralization is concentrated near the injection port, adjust the injection pressure fluctuation range to within ±15% or increase the pulse frequency.
[0023] By adopting the above technical solution, pH, conductivity, and Ca... 2+ Concentration directly reflects the reaction process of calcium carbonate precipitation; NH4 + Concentration, NO3 - The concentration is used to monitor the elimination of secondary pollution. When downstream NH4... + When the concentration rises abnormally, it indicates that the activity of urease-producing bacteria is too strong, while the conversion capacity of ammonia-oxidizing bacteria is insufficient. The system can quickly restore metabolic balance by increasing the proportion of ammonia-oxidizing bacteria or extending the settling time. When mineralization is found to be concentrated near the injection port, it indicates that the fluid resistance is too high. At this time, adjusting the pressure fluctuation range or increasing the pulse frequency can enhance the pulsation effect of the slurry, overcome local blockage, and push the reaction front deeper. This closed-loop system of "monitoring-analysis-control" ensures that the entire barrier construction process always proceeds along the optimal path, ultimately achieving an ideal sealing effect with uniform quality and depth distribution.
[0024] Thirdly, this application provides a biomineralization barrier for sealing bedrock fissures and controlling the back diffusion of pollutant matrix, employing the following technical solution: A biomineralization barrier for sealing bedrock fissures and controlling the back diffusion of pollutant matrix is disclosed. The biomineralization barrier is a calcium carbonate-biochar composite framework structure filled in the bedrock fissures. The composite framework consists of micron-sized biochar particles and calcium carbonate crystals attached to the surface of the biochar particles and the bedrock fissure walls. The biomineralization barrier reduces the equivalent hydraulic conductivity of the target fissure zone by at least two orders of magnitude, and the ammonium ion concentration at the downstream monitoring point is not higher than 10% of the background value.
[0025] By adopting the above technical solution and utilizing the aforementioned construction system and its application method, a highly active and self-healing composite biological barrier system composed of microorganisms, an organic / inorganic framework, and biogenic minerals was constructed. This barrier not only achieves physical sealing, but its dormant microbial community can also be reactivated under suitable environmental conditions to self-repair micro-fractures, thus ensuring the long-term stability and permanence of the sealing effect. A reduction of at least two orders of magnitude in the equivalent hydraulic conductivity coefficient signifies a more than 100-fold improvement in the barrier's impermeability, effectively preventing the back-diffusion of pollutants through fissures with groundwater. The ammonium ion concentration at downstream monitoring points is no higher than 10% of the background value. This indicator directly proves that this application, by introducing ammonia-oxidizing bacteria, effectively solves the technical problem of secondary ammonium ion pollution generated by traditional MIP processes at the source, truly achieving the goal of efficient and environmentally friendly groundwater remediation.
[0026] In summary, this application has the following beneficial effects: 1. Because this application uses a compound functional bacterial agent composed of urease-producing bacteria and ammonia-oxidizing bacteria, and is combined with a three-stage sequential injection process, it achieves the in-situ conversion of metabolic byproduct ammonium ions into harmless nitrate ions while sealing the cracks, thus obtaining the technical effect of highly efficient sealing without secondary pollution.
[0027] 2. In this application, hydrophobic modified silica nanocarriers and modified biochar micron carriers are preferred. By using the combination of the two, a multi-level microbial habitat framework from the nanoscale to the microscale is constructed, thus achieving the technical effect of efficient colonization and long-term survival of functional microorganisms in barren bedrock fissures.
[0028] 3. The method of this application, by adopting a strategy that combines low-pressure pulse injection with real-time monitoring and feedback control, simulates the natural growth law of biofilm and can dynamically optimize injection parameters based on monitoring data. Therefore, it achieves the technical effect of guiding the mineralization reaction to advance uniformly into the depth of the fracture, avoiding the sealing effect, and realizing deep, uniform and controllable sealing. Detailed Implementation
[0029] This invention is not a simple superposition of various technical features, but rather a synergistic design based on microbial colonization-mineralization kinetics and fracture fluid dynamics: nanocarriers solve the initial adhesion problem, micron-carriers provide a three-dimensional osteogenic framework, hydrogels regulate the substrate release rate to match the microbial metabolic cycle, low-pressure pulses maintain unobstructed flow channels and prevent biofilm erosion, and real-time monitoring forms a closed-loop control. The coupling of these four elements achieves simultaneous advancement of "permeation-colonization-mineralization-regulation." The following detailed description, in conjunction with embodiments, further illustrates this application. Furthermore, the data settings for the embodiments and comparative examples in this application are based on a simulated bedrock fracture physical model, with a fracture zone length of 2m and an initial equivalent hydraulic conductivity coefficient of 1×10⁻⁶. -3 The specific parameters (m / s) are set values under laboratory verification conditions. These model parameters are merely illustrative settings, and those skilled in the art can make adaptive adjustments based on actual site conditions (fracture aperture, permeability coefficient, groundwater chemical background, etc.). Preparation Examples of Modified Biochar 1-2
[0030] Preparation Example 1 The method for preparing modified biochar includes the following steps: soaking raw biochar with a particle size of 20-100 μm in a 10 wt% hydrogen peroxide aqueous solution with a solid-liquid ratio of 1:10, shaking and modifying it at 25°C for 4 h, then washing it with deionized water until neutral, and drying it at 105°C to obtain modified biochar.
[0031] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that Preparation Example 2 uses a 5 wt% potassium permanganate solution instead of hydrogen peroxide solution for modification. Preparation Example 3 of Hydrophobic Modified Silica Nanocarriers
[0032] Preparation Example 3 The preparation method of hydrophobic modified silica includes the following steps: 5g of silica nanoparticles with a particle size of 500nm are dispersed in 100mL of anhydrous ethanol, 1mL of silane coupling agent KH-570 and 0.5mL of surfactant sodium dodecyl sulfonate are added, and the mixture is stirred at 60℃ for 6h. After the reaction is completed, the mixture is centrifuged, washed 3 times with anhydrous ethanol, and dried under vacuum at 80℃ to obtain hydrophobic modified silica. Example 4 of the preparation of compound functional microbial agents
[0033] Preparation Example 4 The preparation method of the compound functional microbial agent includes the following steps: culturing Bacillus pasteurellii and Nitrosomonas flavonoids to the required concentrations, with the concentration of the urease-producing bacteria being 5 × 10⁻⁶. 8 CFU / mL, urease activity was 3.2 U / mL; the concentration of ammonia-oxidizing bacteria was 1×10⁻⁶. 8CFU / mL. Urease-producing bacteria and ammonia-oxidizing bacteria were mixed at a volume ratio of 2:1 to prepare a compound functional bacterial agent. Example 5: Preparation of biodegradable hydrogels
[0034] Preparation Example 5 A method for preparing a biodegradable hydrogel includes the following steps: A poly(N-isopropylacrylamide) thermosensitive hydrogel with a phase change temperature of 15°C is compounded with guar gum at a mass ratio of 2:1, resulting in a total concentration of 0.5% (w / v). This mixture is dissolved in deionized water, stirred until homogeneous, and then stored at 10°C to obtain a hydrogel solution. For use, urea and calcium chloride are added to this hydrogel solution and stirred until homogeneous to obtain a three-stage slurry. Example
[0035] The hardware configuration of the system built in the embodiments and comparative examples of this application is as follows: (I) Grout preparation and injection unit The slurry preparation and injection unit includes a slurry preparation subsystem and an injection subsystem. The slurry preparation subsystem consists of a stainless steel preparation tank with a stirring device, a metering and feeding device, and a low-temperature storage device for the microbial agent. It is used to prepare the slurry for stages one, two, and three according to the specified ratio. The injection subsystem consists of a hydraulic grouting pump or a variable frequency speed-regulating grouting pump, injection pipelines, and injection wells or injection point devices. The injection pump has the function of steplessly adjusting the discharge rate and discharge pressure. The injection subsystem receives instructions from the feedback control terminal through a PLC controller to achieve precise control of the injection pressure and flow rate.
[0036] (ii) Distributed monitoring nodes Distributed monitoring nodes are deployed in a network of monitoring wells upstream and downstream of the target fracture zone. The construction of the monitoring wells is carried out in accordance with the "Technical Specification for Groundwater Environmental Monitoring" (HJ 164) and the "Technical Specification for Wells" (GB 50296). Upstream monitoring wells are used to collect background data, while downstream monitoring wells are used to monitor water quality changes in real time during the barrier construction process. Each monitoring well is equipped with an integrated multi-parameter water quality monitoring probe, which can continuously and automatically monitor parameters such as pH, conductivity, temperature, calcium ion concentration, ammonium ion concentration, nitrate ion concentration, and redox potential in situ. The monitoring data is transmitted to the feedback control terminal in real time via wireless communication technology.
[0037] (III) Feedback Control Terminal The feedback control terminal consists of an industrial control computer or server and a Supervisory Control and Data Acquisition (SCADA) system. It connects to the data transmitters of the distributed monitoring nodes and the PLC controllers of the slurry preparation and injection units via wired or wireless communication. The feedback control terminal has built-in data processing and decision-making algorithms that automatically determine the progress of the mineralization reaction and the effect of by-product elimination based on real-time monitoring data. When trigger conditions are met, it issues control commands to the injection units, such as adjusting the inoculant ratio, injection pressure, or pulse frequency, forming a closed-loop control system of "monitoring-analysis-control".
[0038] Example 1
[0039] A system for constructing a biomineralization barrier to control the back diffusion of pollutant matrix in bedrock fractures includes a slurry preparation and injection unit, distributed monitoring nodes (a network of monitoring wells deployed upstream and downstream of the target fracture zone), and a feedback control terminal. The slurry preparation and injection unit is used to prepare and inject biomineralization slurry. The feedback control terminal is communicatively connected to the slurry preparation and injection unit and the distributed monitoring nodes to adjust injection parameters. The method of using the above-mentioned system includes the following steps: S1. Preparation of composite functional bacterial agent and functional carrier material: The composite functional bacterial agent is the composite functional bacterial agent prepared in Preparation Example 4; the functional carrier material includes micron carrier and nano carrier. The micron carrier is the modified biochar prepared in Preparation Example 1, and the nano carrier is the hydrophobic modified silica prepared in Preparation Example 3.
[0040] S2. A three-stage sequential injection process is used to inject sequentially into the target bedrock fracture zone: Stage 1 slurry: includes the composite functional bacterial agent prepared in Preparation Example 4, the nanocarrier prepared in Preparation Example 3, and the microbial activation nutrient solution. The volume ratio of urease-producing bacteria to ammonia-oxidizing bacteria is 2:1, the concentration of the nanocarrier is 0.1% (w / v), the total solute concentration of the microbial activation nutrient solution is 1.0% (w / v), and the molar ratio of urea, calcium chloride, and potassium dihydrogen phosphate is 10:5:1.
[0041] Phase II slurry: This includes the micron-sized carrier prepared in Preparation Example 1, the composite functional bacterial agent prepared in Preparation Example 4, and the microbial nutrient solution. The amount of micron-sized carrier added is 1.5% (w / v), the volume ratio of urease-producing bacteria to ammonia-oxidizing bacteria is 2:1, the total solute concentration of the microbial nutrient solution is 1.5% (w / v), and the molar ratio of urea to calcium chloride is 1:1.
[0042] Stage 3 slurry: includes a biodegradable hydrogel containing urea and calcium ions, wherein the biodegradable hydrogel is selected from the hydrogel solution prepared in Preparation Example 5.
[0043] S3. During the injection process, feedback control is implemented based on real-time monitoring data, and the injection of grout in each stage is completed through a low-pressure pulse injection method. The injection pressure is 0.2 times the fracture hydrostatic pressure. Each injection stage is divided into multiple pulse cycles, each cycle including a short injection of 2 hours and a long settling period of 48 hours. pH, conductivity, and Ca are monitored in real time. 2+ Concentration, NH4 + Concentration, NO3 - Concentration and groundwater tracer breakthrough curves. The feedback control strategy is: when the downstream monitoring point NH4... + When the concentration rise rate exceeds 0.5 mg / L / h or the peak concentration exceeds 5 times the background value, increase the proportion of ammonia-oxidizing bacteria by 15% in the next pulse; when mineralization is concentrated near the injection port, adjust the injection pressure fluctuation range to within ±10%.
[0044] S4. After injection, perform barrier maturation maintenance for 30 days until the equivalent hydraulic conductivity of the target fracture zone is reduced by at least two orders of magnitude.
[0045] Example 2
[0046] The difference between Example 2 and Example 1 is that in Example 2, the micron-sized carrier in step S1 is the modified biochar prepared in Example 2.
[0047] Example 3
[0048] The difference between Example 3 and Example 1 is that in Example 3, the mass ratio of the biodegradable hydrogel temperature-sensitive hydrogel to guar gum in the stage three slurry of step S2 is 1:1.
[0049] Example 4
[0050] The difference between Example 4 and Example 1 is that in Example 4, the mass ratio of the biodegradable hydrogel temperature-sensitive hydrogel to guar gum in the stage three slurry of step S2 is 3:1.
[0051] Example 5
[0052] The difference between Example 5 and Example 1 is that in Example 5, each cycle of the low-pressure pulse injection in step S3 includes a short injection of 4 hours and a long resting period of 72 hours.
[0053] Example 6
[0054] The difference between Example 6 and Example 1 is that in Example 6, each cycle of the low-pressure pulse injection in step S3 includes a short injection of 1 hour and a long rest of 24 hours. Comparative Example
[0055] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the compound functional microbial agent only contains urease-producing bacteria and does not contain ammonia-oxidizing bacteria.
[0056] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the injection of the first stage slurry is omitted, and the injection starts directly from the second stage slurry.
[0057] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, all the slurry components of Stage 1, Stage 2 and Stage 3 are mixed and injected into the target bedrock fracture zone in one go. Performance testing
[0058] The system was constructed and tested on a simulated bedrock fracture physical model according to the construction methods of Examples 1-6 and Comparative Examples 1-3. The fracture zone length of the model was 2m, and the initial value of the equivalent hydraulic conductivity coefficient was 1×10. -3 m / s.
[0059] The following tests were conducted on the biobarrier system after it was constructed and cured for 30 days: 1. Equivalent hydraulic conductivity coefficient test: The equivalent hydraulic conductivity coefficient of the fracture zone after the barrier was constructed was determined by constant head method, and the reduction factor compared with the initial value was calculated. The results are recorded in Table 1.
[0060] 2. Secondary pollution monitoring: Water samples were continuously collected at monitoring points downstream of the barrier system to determine NH4 levels. + The concentration was calculated, and its ratio to the background value (0.5 mg / L) was calculated (i.e., the multiple of the relative background value). The results are recorded in Table 1.
[0061] 3. Assessment of the uniformity of sealing: After the barrier was constructed, five points were taken at equal intervals along the depth of the fissure. The amount of calcium carbonate precipitation at each point was measured, and the coefficient of variation was calculated. The smaller the coefficient of variation, the more uniform the sealing. The results are recorded in Table 1.
[0062] Table 1 Performance test results of the biological barrier system Example 1 185 0.51 1.02 0.13 Example 2 178 0.52 1.04 0.14 Example 3 162 0.53 1.06 0.17 Example 4 158 0.52 1.04 0.18 Example 5 171 0.53 1.06 0.15 Example 6 168 0.52 1.04 0.16 Comparative Example 1 112 4.85 9.70 0.35 Comparative Example 2 28 0.81 1.62 0.52 Comparative Example 3 41 0.75 1.50 0.48 The data comparison of the above comparative examples and embodiments proves that the various technical features of this application have an inseparable synergistic effect within a limited scope, and the absence of a single feature or deviation of parameters will lead to a significant reduction in the technical effect.
[0063] As can be seen from Table 1, Examples 1-6, and Comparative Examples 1-3, the biomineralization barrier systems prepared in Examples 1-6 of this application all exhibit excellent sealing effects and environmental friendliness. Their equivalent hydraulic conductivity is reduced by 158-185 times compared to the original fracture zone, i.e., at least two orders of magnitude, indicating that the barrier system forms an extremely dense sealing layer, effectively preventing the back diffusion of pollutants from the matrix. Simultaneously, the NH4 at downstream monitoring points... + The concentration was only 0.51-0.53 mg / L, almost the same as the background value, and the relative background value multiple was only 1.02-1.06, indicating that the system successfully eliminated NH4 generated by the traditional MIP process at the source. + Secondary pollution. Furthermore, the coefficient of variation for calcium carbonate precipitation was only 0.13-0.18, demonstrating that the mineralization reaction was uniformly distributed along the depth of the fissures, achieving deep sealing rather than surface sealing. This application employs a composite functional bacterial agent combining urease-producing bacteria and ammonia-oxidizing bacteria, along with a three-stage sequential injection process: colonization with nanocarriers, framework construction with micron-carriers, and sustained-release of the substrate via hydrogel. Urease-producing bacteria decompose urea to produce carbonate ions, which combine with calcium ions to form calcium carbonate precipitate, while ammonia-oxidizing bacteria simultaneously release the byproduct NH4. + Converted into pollution-free NO3 - The 2:1 volume ratio of the two components achieved a dynamic balance of metabolites. The hydrophobically modified silica nanocarrier ensured the penetration of the bacterial agent into the depths of the fissures, the modified biochar micron carrier provided a stable habitat framework for the microorganisms, and the thermosensitive hydrogel and guar gum composite system achieved long-term sustained release of the substrate, guiding uniform mineralization.
[0064] Compared to Example 1, the equivalent hydraulic conductivity of Comparative Example 1 decreased by a factor of 112, indicating a significantly worse sealing effect. More importantly, its downstream NH4... + The concentration was as high as 4.85 mg / L, which is 9.70 times the background value, causing serious secondary pollution. This is because the compound functional bacterial agent in Comparative Example 1 only contained urease-producing bacteria and did not add ammonia-oxidizing bacteria. Although urease-producing bacteria can still induce calcium carbonate precipitation to form a certain degree of blockage, the large amount of NH4 produced by their metabolism... + Unable to be converted, resulting in NH4 + It accumulates in large quantities downstream. This not only proves the irreplaceable role of ammonia-oxidizing bacteria in eliminating secondary pollution, but also illustrates the importance of NH4. + The accumulation of these substances may inhibit the activity of the microbial community, indirectly affecting the uniformity and final effect of the blockade.
[0065] Compared with Example 1, Comparative Example 2 omitted the injection of the first-stage slurry, and its equivalent hydraulic conductivity was reduced by only 28 times, resulting in extremely poor sealing effect. Moreover, the coefficient of variation of calcium carbonate precipitation was as high as 0.52, indicating that the sealing was extremely uneven. This is because without the first-stage slurry carrying the nanocarrier, the functional bacterial agent could not obtain an initial attachment site in the depth of the fissure. Most of the bacterial solution was directly lost during subsequent injection or only colonized near the injection port. This resulted in the subsequent second-stage and third-stage slurries being unable to effectively build a framework and carry out mineralization in the depth. Most of the reaction was concentrated near the injection port, forming a "sealing" effect and failing to effectively seal the depth of the fissure.
[0066] Compared to Example 1, Comparative Example 3, which injected all slurry components at once, only saw a 41-fold reduction in its equivalent hydraulic conductivity, but a coefficient of variation as high as 0.48. The sealing effect and uniformity were far inferior to Example 1. This is because the one-time injection violated the principle of gradual sealing. The simultaneous and abundant presence of substrate and microorganisms in the fractures led to an excessively rapid and uncontrollable mineralization reaction rate, resulting in the rapid formation of large amounts of calcium carbonate precipitates near the injection point, physically blocking the slurry's transport channels to deeper fractures. Subsequent nutrients and microorganisms could not reach the depths of the fractures, resulting in a shallow sealing layer concentrated at the injection point, failing to form an effective deep biological barrier.
[0067] Compared with Example 1, Examples 3-4 changed the mass ratio of thermosensitive hydrogel to guar gum in the stage 3 slurry. The blocking effect and uniformity of Examples 3-4 were slightly inferior to those of Example 1. This shows that the compounding ratio of hydrogels has a significant impact on the release rate of the substrate. When the proportion of guar gum is too high, the gel network is too dense, the substrate release is too slow, and the mineralization reaction is insufficient. When the proportion of thermosensitive hydrogel is too high, the stability of the gel structure decreases, and the substrate may experience a burst release phenomenon, resulting in an excessively fast local reaction. The 2:1 compounding ratio in Example 1 achieved the optimal substrate slow-release half-life, guiding the most uniform and sufficient deep mineralization.
[0068] Compared to Example 1, Examples 5-6 altered the pulse cycle of the low-pressure pulsed injection. The blocking effect of Example 5 was slightly lower than that of Example 1, and Example 6 was also slightly worse. This indicates that the pulse cycle of short-time injection followed by long-time rest needs to be optimized. The 2-hour injection / 48-hour rest cycle of Example 1 provides timely nutrient replenishment for microorganisms while offering a sufficiently long undisturbed rest period for attachment, growth, and mineralization. Excessively long injection times may erode the newly formed biofilm, while excessively short rest times are insufficient for microorganisms to fully complete the metabolic and mineralization processes; both will have a slight adverse effect on the final barrier performance.
[0069] In summary, this application has successfully constructed a biomineralization barrier system that can achieve deep, uniform, permanent sealing without secondary pollution through the synergistic effect of specific compound bacterial agents, multi-level carriers, a three-stage sequential injection process, and a low-pressure pulsed feedback control strategy. The comparison results of each embodiment and comparative example strongly demonstrate the synergistic importance and irreplaceability of the key features of the technical solution of this application, especially the compound bacterial agent, the three-stage process, the carrier type, the hydrogel ratio, and the pulse period.
[0070] The above parameter ranges represent the preferred ranges of this invention. Those skilled in the art can make conventional adjustments based on actual formation permeability, groundwater chemical background, and microbial adaptability to achieve the deep uniform sealing and non-secondary pollution effects described in this invention. Examples 1-6 are preferred embodiments, and their data have demonstrated the stability of the technical effects within this range.
[0071] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A system for constructing a biomineralization barrier to seal bedrock fissures and control the back diffusion of pollutant matrix, characterized in that: include: The slurry preparation and injection unit is used to prepare and inject biomineralized slurry; the biomineralized slurry contains a composite functional bacterial agent and a multi-level functional carrier, the composite functional bacterial agent contains urease-producing bacteria and ammonia-oxidizing bacteria, and the multi-level functional carrier includes micron-sized biochar carrier and nano-sized silica carrier. The slurry preparation and injection unit includes at least: a preparation device for providing slurry preparation space, an injection device for delivering slurry to the target fracture zone, and a control device connected to the injection device for adjusting injection parameters. Distributed monitoring nodes are a network of monitoring wells deployed upstream and downstream of the target fracture zone; The feedback control terminal is communicatively connected to the control device and the monitoring node, and is used to adjust the injection parameters of the slurry preparation and injection unit.
2. The system for constructing a biomineralization barrier for sealing bedrock fissures and controlling the back diffusion of pollutant matrix according to claim 1, characterized in that: The distributed monitoring node includes a monitoring probe for real-time acquisition of pH value, conductivity, calcium ion concentration, ammonium ion concentration and nitrate ion concentration.
3. A method of using the construction system as described in any one of claims 1-2, characterized in that, Includes the following steps: S1. Prepare a composite functional microbial agent and a multi-level functional carrier, wherein the composite functional microbial agent contains urease-producing bacteria and ammonia-oxidizing bacteria, and the multi-level functional carrier includes a micron-sized biochar carrier and a nano-sized silica carrier. S2. A three-stage sequential injection process is used to inject sequentially into the target bedrock fracture zone: The first stage slurry includes the aforementioned composite functional bacterial agent, nanocarrier, and microbial activation nutrient solution; The second stage slurry includes the micron-sized carrier, the composite functional bacterial agent, and the microbial nutrient solution; The three-stage slurry includes a biodegradable hydrogel embedded with urea and calcium ions; S3. During the injection process, feedback control is performed based on real-time monitoring data, and the injection of slurry at each stage is completed through low-pressure pulse injection. S4. After injection, barrier maturation and curing are carried out to form a sealed plug layer of calcium carbonate cemented microbial skeleton in the bedrock fracture zone. After curing, the equivalent hydraulic conductivity is reduced by ≥2 orders of magnitude compared with the original value.
4. The method of using the construction system according to claim 3, characterized in that: In step S1, the volume ratio of the urease-producing bacteria to the ammonia-oxidizing bacteria is 2:1; the concentration of the urease-producing bacteria in the bacterial solution is ≥5×10⁻⁶. 8 CFU / mL, urease activity not less than 3.0 U / mL; the bacterial concentration of the ammonia-oxidizing bacteria ≥ 1×10⁻⁶. 8 CFU / mL.
5. The method of using the construction system according to claim 3, characterized in that: In step S1, the micron-sized carrier is modified biochar with a particle size of 20-100 μm, which is obtained by modification with hydrogen peroxide or potassium permanganate; the nano-carrier is hydrophobic modified silica with a particle size of <500 nm, which is silica modified with silane coupling agent surfactant.
6. The method of using the construction system according to claim 3, characterized in that: In the first stage slurry, the volume ratio of urease-producing bacteria to ammonia-oxidizing bacteria is 2:1, the concentration of nanocarrier is 0.1% (w / v), the total solute concentration of microbial activation nutrient solution is 1.0% (w / v), and the molar ratio of urea, calcium ions and phosphorus source is 10:5:
1. In the second stage slurry, the amount of micron-sized carrier added is 1.5% (w / v), the volume ratio of urease-producing bacteria to ammonia-oxidizing bacteria is 2:1, the total solute concentration of the microbial nutrient solution is 1.5% (w / v), and the molar ratio of urea to calcium ions is 1:
1.
7. The method of using the construction system according to claim 3, characterized in that: In step S2, the biodegradable hydrogel is a compound system of thermosensitive hydrogel and guar gum, with a total concentration of 0.5% (w / v) and a mass ratio of thermosensitive hydrogel to guar gum of (1-3):1; the phase transition temperature of the thermosensitive hydrogel is 10-20℃.
8. The method of using the construction system according to claim 3, characterized in that: In step S3, the pressure of the low-pressure pulse injection is less than 0.3 times the fracture hydrostatic pressure; each injection stage is divided into multiple pulse cycles, each cycle including a short injection of 1-4 hours and a long settling period of 24-72 hours.
9. A method for using a construction system according to claim 3, characterized in that: In step S3, the real-time monitoring data includes pH, conductivity, and Ca. 2+ Concentration, NH4 + Concentration, NO3 - Concentration and groundwater tracer breakthrough curve; the feedback control includes: When the rate of increase of NH4+ concentration at downstream monitoring points exceeds 0.5 mg / L / h or the peak concentration exceeds 5 times the background value, the mass ratio or molar ratio of ammonia-oxidizing bacteria in the slurry to the total inoculum in the next stage should be increased by 10-20%, or the static incubation time should be extended by 12-24 h. When mineralization is concentrated near the injection port, adjust the injection pressure fluctuation range to within ±15% or increase the pulse frequency.
10. A biomineralization barrier for sealing bedrock fissures and controlling the back diffusion of pollutant matrix, characterized in that: The biomineralization barrier is a calcium carbonate-biochar composite framework structure filled in bedrock fissures. The composite framework consists of micron-sized biochar particles and calcium carbonate crystals attached to the surface of the biochar particles and the bedrock fissure walls. The biomineralization barrier reduces the equivalent hydraulic conductivity of the target fissure zone by at least two orders of magnitude, and the ammonium ion concentration at the downstream monitoring point is not higher than 10% of the background value.